Development of serological technique for examination of aspergillosis in chicken - Gholib, Djaenudin (Indonesian Animal Sciences Society, 2005)
Aspergillosis detection by using serological method has not been reported in Indonesia. In this case, a study was conducted, by using mycelium extract of A. fumigatus as the antigen. Rabbits and chickens were injected with the antigen to produce positive serum (antiserum). The antigen and antiserum were tested serologicaly by Immunodiffusion/Agar Gel Precipitation (AGP), ELISA and Immunoblot. Chicken serum of broiler and layer collected from field were also included in the test. All positive serum of the experimentally animals gave positive results with all methods of serological tests. No bands of precipitation reaction in AGP test with chicken serum from the field. Both chicken and rabbit positive serum with ELISA test showed high Optical Density (OD), while field chicken serum from broiler commonly gave lower OD compared to layer. Immunoblot test of chicken positive serum showed bands of reaction with the antigen in nitrocellulose membrane, approximately on 33, 38, 44, 52, 70, 77, 97, and 110 kDa, meanwhile field chicken serum with high OD in ELISA test, showed bands approximately on 16, 18, 33, 38, 44, 47, 52, 70, 77, 84, 97, and 110 kDa. It means that the field chicken serum contain immunoglobulin molecules has spesific antibody of aspergillus antigen. It is concluded that the ELISA test can be used for screening on chicken aspergillosis in serological methode. Â Â Key Words: Antigen, Aspergillus fumigatus, Serology, Chicken